Documenting the Impact of Conflict on Women Living in Internally Displaced Persons Camps in Sri Lanka: Some Ethical Considerations - Shana Swiss; Peggy J. Jennings; K. G. K. Weerarathne; Lori Heise (Harvard FXB Center for Health and Human Rights, 2019)
Women's Rights International works with rural women and girls who are living in countries at war or with ongoing political violence. In 2005, The Asia Foundation invited Women's Rights International to Sri Lanka to evaluate the feasibility of a random-sample survey of women to document the impact of the decades-long conflict. The significant imbalance in the risks-to-benefits ratio compelled us to recommend that random-sample surveys that included questions about sexual violence be avoided at that time, especially in the displaced persons areas. Instead, we recommended that three strategies be given priority in situations in which the risks for women are too great to justify a random-sample survey. First, maximize the use of existing information. Second, collect survey data only in partnership with a strong community organization that will use the data for direct tangible benefits. Third, share knowledge that will help build the capacity of local organizations to design surveys that address their priorities, and collect and use their own data following ethical guidelines that maximize the protection of individuals and the wider community. We implemented these recommendations in a partnership with a local organization with a strong history of advocating for women's rights.